Effect of different fertilizer sources on the yield and fiber quality of Musa textilis ‘Tangongón’ - Jácome , Leonardo; Jácome , Janeth; Martínez , María; De La Cruz, Marco; Chica , Holger (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The fertilization of abacá through the application of organic and chemical fertilizers influences fiber production, but its combined effect still requires evaluation. This research evaluated the effect of different fertilizer sources on the fiber production of the ‘Tangongón’ abacá in Santo Domingo de los Tsáchilas, Ecuador, to determine the most efficient alternative for improving abacá fiber yield and quality. A randomized complete block design with a 2×3 factorial arrangement and four replications was used. Two soil fertilizers and three foliar fertilizer conditions were evaluated, and growth, yield, and fiber quality variables were analyzed. Fertibanano without foliar supplementation stood out for achieving the highest fiber yield (1.25 t.ha-1.year-1) and for producing the highest proportion of higher-quality fiber (2.nd quality = 0.307 kg.pseudostem-1). Furthermore, it generated the highest averages of suckers.plant-1 (2.13) and shoots.plant-1 (7.25). Although the combination of Ecoabonaza with Bayfolan promoted the greatest plant height (1.58 cm.month-1), and Fertibanano with humic acids showed the highest values ​​in the number of leaves.plant-1 (0.85) and pseudostem circumference (2.59 cm), these treatments exhibited lower fiber yield and a lower proportion of second-quality fiber. It was concluded that nutritional management based on Fertibanano constitutes a nutritional strategy to optimize the yield and quality of abacá fiber.